Critical transport and critical scattering in ﬂuids - Folk, R. (Condensed Matter Physics, 2000)
We consider the critical properties of ﬂuids induced by the critical ﬂuctuations in the order parameter. The theory describes the crossover from
the analytic background behaviour to the universal asymptotic behaviour
of several dynamic quantities. Розглядаються критичні властивості плинів, що індуковані критичними флюктуаціями параметра порядку. Теорія описує кросовер від
аналітичної фонової поведінки до асимптотичної поведінки для кількох динамічних величин.